Spillover Implications of Differences in Monetary Conditions in the United States and the Euro Area - Osorio Buitron, Carolina; Vesperoni, Esteban (Washington, D.C. : International Monetary Fund, 2016)
This report analyzes the possible spillover effects that could result if the U.S. normalizes its monetary policy while euro area countries are increasing monetary stimulus (a situation referred to as asynchronous monetary conditions). This analysis identifies country-specific shocks to economic activity and monetary conditions since the early 1990s, finding that real and monetary conditions in the United States and the euro area have oftentimes been asynchronous and have often resulted in significant spillover effects, particularly since early 2014.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet